Odpowiedzi

2009-12-29T11:02:01+01:00
2 /√6 - √2 =
w tego typu przykładach korzystamy ze wzoru:
x² - y² = (x+y)(x-y)
Czyli ten ułamek musimy rozszerzyć przez ( √6 + √2)

2(√6 + √2) /(√6 - √2)(√6 + √2) = 2(√6 + √2) /( √6)² - (√2)² =
2(√6 + √2)/ 6 - 2 = 2(√6 + √2)/4 = skracamy przez 2 = (√6 + √2)/2
2009-12-29T11:02:30+01:00
2
-------- =
√6-√2


2
= -------- ×
√6-√2

√6+√2
× --------- =
√6+√2


2(√6+√2)
= -------------- =
√36-√4


2(√6+√2)
= ----------- =
6-2



2(√6+√2)
= -------------- =
4

√6+√2
= -------------
2
2009-12-29T11:03:23+01:00
2/(√[6]-√[2])=2/(√[6]-√[2]) *(√[6]+√[2])/(√[6]+√[2])=
=(2*(√[6]+√[2])/(6-2)= (√[6]+√[2])/2